2021
DOI: 10.1016/j.cell.2021.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Elevated rates of horizontal gene transfer in the industrialized human microbiome

Abstract: Highlights d Thousands of gut bacterial genomes from worldwide human populations were sequenced d HGT occurs at high frequency in the gut microbiome of individual persons d HGT occurs more frequently in the microbiome of industrialized and urban populations d Transferred gene functions in the microbiome reflect the lifestyle of the host

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
193
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(204 citation statements)
references
References 87 publications
11
193
0
Order By: Relevance
“…We assumed a recent (i.e. within the lifetime of the participant) intra-host transfer event if shared GA2 DNA regions are >99.99% identical [ 11 , 18 ]. Shared T6SS regions between two species indicated a single-species spread event, whereas we inferred multi-species spread if the identical region was found in at least three different species from the same community.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assumed a recent (i.e. within the lifetime of the participant) intra-host transfer event if shared GA2 DNA regions are >99.99% identical [ 11 , 18 ]. Shared T6SS regions between two species indicated a single-species spread event, whereas we inferred multi-species spread if the identical region was found in at least three different species from the same community.…”
Section: Resultsmentioning
confidence: 99%
“…One caveat to note is that our MGE spread analysis was conducted using four datasets from industrialized lifestyles, largely from Bacteroides -dominated communities. Analyses of HGT events in Prevotella -dominated non-industrialized populations indicated less frequent HGT [ 18 ] and may show a different repertoire of MGEs and different frequency of multi-species spread.…”
Section: Resultsmentioning
confidence: 99%
“…These studies have largely concluded, although with some debate ( Andreani et al 2017 ; Shapiro 2017 ) that pangenomes are predominantly adaptive—that selection plays a bigger role in pangenome evolution than drift. Here we have refocused the study of pangenome evolution to shorter time scales that is within individual gut microbiomes in which gene transfer events likely occurred within a human lifespan ( Brito et al 2016 ; Groussin et al 2021 ). Based on microbiome data from a Fiji cohort, we found that mobile gene sequence evolution is more influenced by selective pressures at the level of gene function than at the human host level.…”
Section: Discussionmentioning
confidence: 99%
“…To fill this gap, we used a data set of 37,853 mobile genes involved in recent HGT events in the human gut ( Brito et al 2016 ). HGT is known to occur frequently within individual human gut microbiomes ( Smillie et al 2011 ; Yaffe and Relman 2020 ; Groussin et al 2021 ), making it an ideal system in which to study mobile gene evolution over short time scales. We mapped metagenomic reads from a cohort of 176 Fiji islander gut microbiomes to the set of mobile genes.…”
Section: Introductionmentioning
confidence: 99%
“…The limited data that are available for these intermediate populations, such as individuals living in peri-urban towns in Peru and South Africa as well as an Irish indigenous group transitioning away from nomadic living, exhibit gut microbial signatures from both highly industrialized and traditional populations but also display features of their own ( 16 , 63 , 64 ). Similarly, a recent worldwide survey found gut microbial composition clustered by lifestyle, with urban nonindustrialized and rural industrialized falling between the more stereotypical urban industrialized and rural nonindustrialized populations ( 65 ). These intermediate microbial signatures are typically ascribed to lifestyle factors, and while human-animal interactions are not always explicitly measured, they may be reflected in the factors found to be significant.…”
Section: Variation In Human Microbial Communities Across Populationsmentioning
confidence: 97%